2021
DOI: 10.3389/fimmu.2021.673248
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Next-Generation Sequencing Combined With Circulating-Free DNA Deciphers Spatial Heterogeneity of Resected Multifocal Hepatocellular Carcinoma

Abstract: BackgroundHepatocellular carcinoma (HCC) has a high risk of recurrence after surgical resection, particularly among patients with multifocal HCC. Genomic heterogeneity contributes to the early recurrence. Few studies focus on targeted next-generation sequencing (tNGS) to depict mutational footprints of heterogeneous multifocal HCC.MethodsWe conducted tNGS with an ultra-deep depth on 31 spatially distinct regions from 11 resected multifocal HCC samples. Matched preoperative peripheral circulating-free DNA (cfDN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Circulating viral-host chimera ctDNA is quickly becoming a valuable diagnostic and prognostic tool in virus-associated cancers, including HPV-associated oropharyngeal carcinoma and cervical cancer and hepatitis B virus–associated hepatocellular carcinoma. Integrated viral ctDNA sequences allow ultrasensitive detection without background interference, may provide tumor location through virus tropism, and can be used to monitor clonal expansion in tumors related to oncogenic viruses 37,56–76 . Furthermore, specific viral integration sites into the cellular genome (integration “hotspots”) may provide information about the tumor phenotype 75 …”
Section: Opportunities For the Futurementioning
confidence: 99%
“…Circulating viral-host chimera ctDNA is quickly becoming a valuable diagnostic and prognostic tool in virus-associated cancers, including HPV-associated oropharyngeal carcinoma and cervical cancer and hepatitis B virus–associated hepatocellular carcinoma. Integrated viral ctDNA sequences allow ultrasensitive detection without background interference, may provide tumor location through virus tropism, and can be used to monitor clonal expansion in tumors related to oncogenic viruses 37,56–76 . Furthermore, specific viral integration sites into the cellular genome (integration “hotspots”) may provide information about the tumor phenotype 75 …”
Section: Opportunities For the Futurementioning
confidence: 99%
“…Increased shedding of ctDNA from more aggressive, resistant clones into the blood has been reported in adult patients with breast, gastro-intestinal (GI), and lung cancer (60-62). Multi-regional tissue sequencing compared to cfDNA in adult non-small cell lung cancer (NSCLC) (60) and hepatocellular carcinoma (63)(64)(65) showed that ctDNA reflects the truncal-branching hierarchy determined by tissue sequencing but it does so incompletely. In the paediatric setting there is very little information to date about the potential of cfDNA to assess the spatial heterogeneity of tumours.…”
Section: Potential Future Applications Of Cfdna Snv and Cnv Profiling...mentioning
confidence: 99%
“…As HCC has many etiological causes and experience a long evolutionary process, the somatic mutation spectrum is heterogeneous (8,98). For example, the mutation in the gene of telomerase reverse transcriptase (TERT) is universal in HCC patients, but its mutation site and patterns are significantly different between HCC patients caused by chronic HBV infection and those caused by alcohol or HCV (99)(100)(101). The high-frequent single-gene mutations in HCV-or alcohol-induced HCC are rarely detected in HBV-induced HCC, suggesting the different mechanisms of cancer evolution.…”
Section: The Role Of Cancer Evo-dev On Guiding Molecular Typingmentioning
confidence: 99%